ANALISIS STRATEGIS KEBIJAKAN HILIRISASI MINERAL: Implikasi Ekonomi dan Pengaruhnya terhadap Perekonomian Indonesia - Ferdinand Tharorogo Wau; Mario Andrias Kiton; Marselino Wau; Jhon Firman Fau (Journal Publicuho, 2024)
Mineral downstreaming is a strategic policy aimed at increasing the value-added of mineral products and optimizing the utilization of natural resources. This policy aims to reduce the export of raw ore and increase the production of finished goods domestically, which has significant potential to secure national foreign exchange reserves and strengthen Indonesia's competitiveness in the global market. This study aims to analyze the implications and impacts of mineral downstreaming policy on the Indonesian economy. The method used is a literature review with a qualitative descriptive approach. The research findings indicate that by promoting further processing and innovation in technology development, nickel downstreaming not only has positive economic impacts through increased revenues in the non-oil and gas sector and corporate contributions to government revenues but also significantly contributes to environmental sustainability. The development of nickel downstream industries not only creates new job opportunities and reduces unemployment rates but also stimulates growth in related industries and enhances the demand for domestic technology.